Multimedia Super Corridor ([S.l.] : National Technology Council)
Malaysia welcomes you to the Multimedia Super Corridor (MSC), a world-first platform for you to join leading companies in building a unique multimedia and information technology environment.
Project director, Al-Ishal Ishak
Narrator: Rodney Fernandez
Keywords: Multimedia Super Corridor; Multimedia systems